Assessment of Fatigue Characteristic of Asphalt Mixture with the Existing of Moisture: A Review - Mat Nor, Nor Najiha Izzati; Mustafa Kamal Shamshuddin (Recent Trends in Civil Engineering and Built Environment, 2021)
Fatigue is one of the most common distress mode of asphalt concrete pavement that cause by the number of load repetitions with high axle loads, environmental conditions, construction quality and design errors [1]. The objectives of this study is to assess the effect of moisture on fatigue characteristic and evaluate the capability of additives in asphalt concrete to resist the effect of moisture. This paper aims to highlight the previous study on the fatigue characteristics and effectiveness of asphalt concrete with the existing of moisture. From the observation of the previous study, the fatigue characteristic of asphalt concrete could be improved by utilization of additives materials such as polyethylene terephthalate, fly ash, polyethylene, silica fumes, nano silica, hydrated lime and asphlatite. Experimental study need to be conducted according to the specification and standard of test method that was stated in the previous study to establish confirmation and verification of their result while the findings show that the uses of additives in asphalt concrete can improve the fatigue characteristic and prolong the performance of the AC pavement.